Nuclear protein 1 imparts oncogenic potential and chemotherapeutic resistance in cancer. (1st December 2020) - Murphy, Anthony; Costa, Max
Abstract: Nuclear protein 1 (NUPR1) also known as p8 and candidate of metastasis 1 (COM1) functions as a transcriptional regulator, and plays a role in cell cycle, DNA damage response, apoptosis, autophagy, and chromatin remodeling in response to various cellular stressors. Since it was first suggested to contribute to cancer development and progression in 1999, a number of studies have sought to reveal its function. However, NUPR1 and its biological relevance in cancer have proven difficult to pinpoint. Based on evidence of NUPR1 expression in cancers, its function extends from carcinogenesis and tumorigenesis to metastasis and chemotherapeutic resistance. A tumor suppressive function of NUPR1 has also been documented in multiple cancers. By and large, literature involving NUPR1 and cancer is confined to pancreatic and breast cancers, yet significant progress has been made with respect to NUPR1 expression and its function in lung, colorectal, blood, and prostate cancers, among others. Recent evidence strongly supports the notion that NUPR1 is key in chemotherapeutic resistance by mediating both anti-apoptotic activity and autophagy when challenged with anti-cancer compounds. Therefore, it is of significant importance to understand the broad range of molecular functions directed by NUPR1. In this review, NUPR1 expression and its role in breast, lung, and colorectal cancer development and progression will be addressed. Highlights: NUPR1 is often overexpressed in breast, lung, and colorectal cancers, among other cancers. NUPR1 overexpression contributes to carcinogenesis, tumorigenesis, metastasis, and chemotherapeutic resistance. NUPR1 confers chemotherapeutic resistance by mediating autophagy, anti-apoptosis, and the ER stress response. Genetic or pharmacological inhibition of NUPR1 is a novel and promising new strategy to treat cancers.